Tropical peanut maturation scale for harvesting seeds with superior quality - Fonseca de Oliveira, Gustavo Roberto [UNESP]; Amaral da Silva, Edvaldo Aparecido [UNESP] (Frontiers, 2024)
Determining the moment for harvesting the tropical peanut with a focus on superior seed quality is not an easy task. Particularities such as indeterminate flowering, underground fruiting and uneven maturation further increase this technical challenge. It is in this context that we aim to investigate harvest indicators based on the maturation and late maturation phases of tropical peanuts to obtain seeds with superior physiological and health quality. The plants were grown in field conditions and their development stages were carefully monitored until seed production. The water content, dry weight, germination capacity, desiccation tolerance, vigor, longevity, and seed pathogens were evaluated throughout these stages. We showed that seeds from early stages (R5 and R6) did not fully tolerate desiccation and were highly sensitive to pathogen contamination after storage (Aspergillus, Penicillium, and Bacteria). At late stages (R7, R8, and R9), the seeds had optimized vigor, longevity and bioprotection against fungi and thermal stress. The peanut maturation scale for tropical agriculture provides unique harvesting guidelines that make it possible to monitor the plants’ development stages with a focus on producing superior quality seeds.
Keywords: Arachis hypogaea L; maturation profile board; optimum peanut digging; peanut seed stages; seed development